THE EFFECTIVENESS ANALYSIS OF MEDICATION BOOKLET ON ADHERENCE RATE IN TYPE 2 DIABETES MELLITUS PATIENTS - Atika Wahyu Puspitasari; Retnosari Andrajati; Anton Bahtiar (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by elevation of blood glucose concentration. Non-adherence to diabetes treatment in type 2 DM patients leads to poor glucose control and increases the risk of disease complications. Education is one of the ways to increase medication adherence. Limitation of pharmacists in public primary health care in Indonesia led to education could not be done effectively so that it was necessary to find other alternatives education such as medication booklet. This study was undertaken to evaluate the effect of a medication booklet on adherence rate parameters, in type 2 diabetic patients. This was pre-experimental and prospective study conducted at Bakti Jaya primary care, Depok from January to June 2012. A convenience sample of 30 type 2 diabetic patients was studied to receive medication booklet. The value of The 8-item Morisky Medication Adherence Scale (MMAS-8) and percentage of glycosylated haemoglobin (HbA1C) were measured before and after the 8-week intervention. The results were analyzed by paired t-test for HbA1C and Wilcoxon test for MMAS-8. The research result showed that there were significant differences (p < 0.05) of the value of HbA1C and MMAS-8 between before and after the 8-week intervention. It indicated that a diabetes education by medication booklet, was effective enhancing their medication adherence. This study also found that patients with a lower score on the Morisky scale had a lower HbA1C measurement.Keywords : MMAS-8, HbA1C, adherence, blood glucose, type 2 diabetes mellitus, booklet, pharmacist